Assessing students’ attitudes and perception towards statistics subject / Siti Hasma Hajar Mat Zin, Rumaizah Che Md Nor and Siti Haslini Zakaria - Mat Zin, Siti Hasma Hajar; Md Nor, Rumaizah Che; Zakaria, Siti Haslini (2023)
Statistics has always been regarded as one of the most difficult subjects for students to master. There are several factors that cause difficulties in understanding the statistics subject, including attitude, perception, expectation, motivation, as well as students' intellectual capability to do well in this subject. Basically, students will have difficulty in learning the subject effectively if they have a negative attitude or perception towards that subject. On that note, a study on assessing students' conceptual understanding, attitudes, and perceptions towards statistics subjects among Universiti Teknologi MARA (UiTM) students was conducted. Primary data is collected by distributing questionnaires to the respondents. Findings revealed that most of the respondents agreed with all statements regarding attitudes and perceptions towards the subject of statistics.